Dimers of N‐Heterocyclic Carbene Copper, Silver, and Gold Halides: Probing Metallophilic Interactions through Electron Density Based Concepts. Issue 3 (11th December 2013) - Pinter, Balazs; Broeckaert, Lies; Turek, Jan; Růžička, Aleš; De Proft, Frank
Abstract Homobimetallic metallophilic interactions between copper, silver, and gold‐based [(NHC)MX]‐type complexes (NHC=N‐heterocyclic carbene, i.e, 1, 3, 4‐trimethyl‐4, 5‐dihydro‐1H‐1, 2, 4‐triazol‐5‐ylidene; X=F, Cl, Br, I) were investigated by means of ab initio interaction energies, Ziegler–Rauk‐type energy‐decomposition analysis, the natural orbital for chemical valence (NOCV) framework, and the noncovalent interaction (NCI) index. It was found that the dimers of these complexes predominantly adopt a head‐to‐tail arrangement with typical M⋅⋅⋅M distance of 3.04–3.64 Å, in good agreement with the experimental X‐ray structure determined for [{(NHC)AuCl}2], which has an Au⋅⋅⋅Au distance of 3.33 Å. The interaction energies between silver‐ and gold‐based monomers are calculated to be about −25 kcal mol−1, whereas that for the Cu congener is significantly lower (−19.7 kcal mol−1). With the inclusion of thermal and solvent contributions, both of which are destabilizing, by about 15 and 8 kcal mol−1, respectively, an equilibrium process is predicted for the formation of dimer complexes. Energy‐decomposition analysis revealed a dominant electrostatic contribution to the interaction energy, besides significantly stabilizing dispersion and orbital interactions. This electrostatic contribution is rationalized by NHC(δ+)⋅⋅⋅halogen(δ−) interactions between monomers, as demonstrated by electrostatic potentials and derived charges. The dominant NOCV orbital indicates weakening of the π backdonation in the monomers on dimer formation, whereas the second most dominant NOCV represents an electron‐density deformation according to the formation of a very weak M⋅⋅⋅M bond. One of the characteristic signals found in the reduced density gradient versus electron density diagram corresponds to the noncovalent interactions between the metal centers of the monomers in the NCI plots, which is the manifestation of metallophilic interaction.